The safer chemical design game. Gamification of green chemistry and safer chemical design concepts for high school and undergraduate students. Issue 2 (3rd April 2018) - Mellor, Karolina E.; Coish, Philip; Brooks, Bryan W.; Gallagher, Evan P.; Mills, Margaret; Kavanagh, Terrance J.; Simcox, Nancy; Lasker, Grace A.; Botta, Dianne; Voutchkova-Kostal, Adelina; Kostal, Jakub; Mullins, Melissa L.; et al.
ABSTRACT: Green chemistry can strongly attract students to chemistry. We, therefore, developed a green chemistry educational game that motivates students at the undergraduate and advanced high school levels to consider green chemistry and sustainability concerns as they design a hypothetical, chemical product. The game is intended for incorporation into any chemistry course for majors and non-majors that teaches sustainability and/or the Principles of Green Chemistry at the undergraduate level. The game is free of charge and encourages students to think like professional chemical designers and to develop a chemical product with respect to function and improved human and environmental health. This computer simulation has been assessed by educators and can be seamlessly integrated into an existing curriculum. GRAPHICAL ABSTRACT: